Strategi Customer Relationship Management dalam Membangun Loyalitas Pelanggan: Studi Kasus TravelKif dengan Pendekatan Model IDIC - Juwita Permata Sari; Heni Hayat (Jurnal EMT KITA, 2026)
PT Solutravel Jelajah Dunia (TravelKif) is a tour operator company that has provided travel packages to Europe since 2016. Amid increasing competition in the tourism industry and the impact of the COVID-19 pandemic, TravelKif has successfully maintained customer loyalty through the implementation of Customer Relationship Management (CRM). This study aims to analyze the CRM strategy implemented by TravelKif in maintaining customer loyalty using the IDIC model (Identify, Differentiate, Interact, Customize) proposed by Peppers and Rogers. This research employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research participants consisted of internal company representatives and TravelKif customers. The findings reveal that TravelKif has implemented all stages of the IDIC model in its CRM strategy. The identification stage was carried out through customer data collection and interaction history, differentiation was based on customer needs and loyalty, interaction was conducted through personal and continuous communication, while customization was implemented through personalized travel services based on customer preferences. The study found that the interaction stage was the most dominant factor in maintaining customer loyalty, as it fostered emotional engagement and long-term relationships. These findings indicate that a relationship-based CRM approach can serve as an effective strategy for tourism companies in maintaining customer loyalty amid industry competition and changing post-pandemic consumer behavior.